Penggunaan Active Learning Tipe Card Sort Terhadap Hasil Belajar Biologi - Desriana Desriana; Elijonnahdi Elijonnahdi; Hidayati Suhaili; Titi Sartini (BIOEDUSAINS:Jurnal Pendidikan Biologi dan Sains, 2023)
This research aims to determine the effect of using card sort type active learning on Biology learning outcomes for class X SMA N 1 Palembayan students. This type of research uses a quassy experiment. The population in this study was 60 students. Sampling was carried out using a purposive sampling technique so that class X.1 was obtained as the experimental class and X.2 as the control class. The research instrument is an objective test consisting of 35 questions. The research results show that the data processing of the final test results is calculated using the t-test with the test criteria of accepting Ho if tcount<ttable and accepting H1 if tcount>ttable. From data analysis, it is obtained that tcount= 2.07 and ttable for the 1-α probability is 1.68, because tcount > ttable. In conclusion, there is a significant positive influence from the use of card sort type active learning on Biology learning outcomes for class X SMA N 1 Palembayan students. Keywords: Biology Learning Results, Use of Card Sort Type Active Learning